Education on clean and healthy living behavior for elementary school students - Arga Buntara; Ulya Qoulan Karima (Community Empowerment, 2023)
Most types of diseases that often attack school-age children are generally related to Clean and Healthy Behavior Practices (PHBS), so it is important to instill PHBS values in schools. The practices of PHBS among SD Islam Serambi Depok students remained suboptimal and specific education about PHBS has never been carried out. The purpose of this community service was to increase students' knowledge about PHBS in schools by educating them on two main topics: 1) PHBS indicators in schools, and 2) advising and strengthening teachers regarding PHBS practices in schools. The education method was carried out by direct counseling in the classroom to 24 elementary school students in grades 4, 5, 6. The results of the program showed an increase in knowledge in the good knowledge category from 29.2% to 75%. After this education, it is suggested that schools continue to monitor PHBS activities and prepare facilities and infrastructure to support PHBS practices.